THE DISAPPEARANCE OF REFUGEE RIGHTS IN SOUTH AFRICA - Callixte Kavuro (Obiter, 2022)
This article critically examines the nature and scope of the type of refugee protection offered by South Africa to people fleeing their home countries. It offers an analytical demonstration of how South Africa has gradually developed conflicted and ambivalent attitudes towards the protection of refugees and asylum seekers. South Africa’s conflicted and ambivalent attitudes towards refugee protection are evident in several amendments made to the refugee regime, to restrict the enjoyment of refugees’ socio-economic protection. The purpose of this article is therefore to demonstrate that the ongoing amendments to the refugee legal framework – without harmonisation with socio-economic laws – increasingly result in the disappearance of refugee rights. This, in turn, results in the creation of disgruntled refugees; through protests, they express their dissatisfaction with ineffective protection, and consequently demand to be resettled or relocated to other countries for better and effective protection.